2018
DOI: 10.1124/dmd.118.083329
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrative Nucleoside Transporter 1 (ENT1, SLC29A1) Facilitates Transfer of the Antiretroviral Drug Abacavir across the Placenta

Abstract: Abacavir is a preferred antiretroviral drug for preventing mother-to-child human immunodeficiency virus transmission; however, mechanisms of its placental transfer have not been satisfactorily described to date. Because abacavir is a nucleoside-derived drug, we hypothesized that the nucleoside transporters, equilibrative nucleoside transporters (ENTs, ) and/or Na-dependent concentrative nucleoside transporters (CNTs, ), may play a role in its passage across the placenta. To test this hypothesis, we performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 60 publications
(117 reference statements)
2
26
0
Order By: Relevance
“…ENTs are widely expressed in various tissues, and ENTs contribute to the transport of endogenous nucleosides and various anticancer and antiviral nucleoside drugs, such as adenosine, gemcitabine, ribavirin, and abacavir (27)(28)(29)(30). Our data revealed that NBTI and dipyridamole (two ENT-specific inhibitors) strongly inhibited FTC uptake in BeWo cells and PHTCs and that NBTI inhibited FTC accumulation in JEG-3 cells (see Fig.…”
Section: Discussionsupporting
confidence: 50%
“…ENTs are widely expressed in various tissues, and ENTs contribute to the transport of endogenous nucleosides and various anticancer and antiviral nucleoside drugs, such as adenosine, gemcitabine, ribavirin, and abacavir (27)(28)(29)(30). Our data revealed that NBTI and dipyridamole (two ENT-specific inhibitors) strongly inhibited FTC uptake in BeWo cells and PHTCs and that NBTI inhibited FTC accumulation in JEG-3 cells (see Fig.…”
Section: Discussionsupporting
confidence: 50%
“…13 ENT1 protein was found to be the predominant nucleoside transporter in placental MVMs (Table 1), as has already been confirmed at the functional and expressional levels. [8][9][10][11][12][13] The expression of ENT2 protein at human placental MVMs was under the limit of quantification according to our quantification analysis criteria, but this does not directly mean the absence of ENT2 protein. In fact, a positive peak was detected for 3 of 4 donors when only the most sensitive SRM transition for human ENT2 was considered, with a mean value of 0.74 fmol/mg protein (Supplemental Table S2).…”
Section: Discussionmentioning
confidence: 91%
“…11 In the rat placental barrier, the functional expression of ENT2 in placental MVM vesicles was suggested by the observation that adenosine uptake is more potently inhibited by NBMPR at 100 mM than at 0.1 mM, 10 which is inconsistent with the observation in human placental MVMs. 12 The involvement of CNTs in the uptake of the nucleoside was undetected neither in rat placental MVM vesicles. 10 Absolute quantification of nucleoside transporter proteins in placental MVMs using liquid chromatography-tandem mass spectrometry (LC-MS/ MS) should enable us to resolve these discrepancies and estimate the transport capacities of individual transporters at the placental MVMs based on the absolute protein expression levels.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations